2022
DOI: 10.1186/s40798-022-00487-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ageing on Female Metabolic Flexibility: A Cross-Sectional Pilot Study in over-60 Active Women

Abstract: Background Ageing affects metabolic flexibility, although physical status could influence this relationship. This cross-sectional study aims to describe and analyse the metabolic flexibility/inflexibility in a group of active older women, together with the impact of ageing and physical status on their oxidation rates and maximal fat oxidation (MFO). Methods Fifteen volunteers (69.00 ± 6.97 years)—from 24 women—completed an incremental cycling test … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(52 reference statements)
1
2
0
Order By: Relevance
“…These latter studies underscore the signi cant importance of the autonomic resources at rest for subsequent physical performance, at least at submaximal intensities. In our sample, with maintained metabolic exibility despite the lower energy expenditure (Blasco-Lafarga et al, 2022), this higher physical performance associated with autonomic resources is observed as higher peak fat oxidation at FATmax, together with higher lactate production at submaximal intensities, which in turn is associated with greater total power(Monferrer-Marín et al, 2022). This connection between metabolic exibility and autonomic health reinforces the autonomic resources hypothesis of Hynynen et al(Hynynen et al, 2008).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…These latter studies underscore the signi cant importance of the autonomic resources at rest for subsequent physical performance, at least at submaximal intensities. In our sample, with maintained metabolic exibility despite the lower energy expenditure (Blasco-Lafarga et al, 2022), this higher physical performance associated with autonomic resources is observed as higher peak fat oxidation at FATmax, together with higher lactate production at submaximal intensities, which in turn is associated with greater total power(Monferrer-Marín et al, 2022). This connection between metabolic exibility and autonomic health reinforces the autonomic resources hypothesis of Hynynen et al(Hynynen et al, 2008).…”
supporting
confidence: 83%
“…Similarly, major interest has been focused on metabolic exibility, or rather its dysfunction, the metabolic in exibility (Frandsen et al, 2021), the latter being an impaired ability to switch energy substrates in response to physiological demands (Galgani et al, 2008). This dysfunction (in exibility) is accompanied by a downward and leftward shift of the energy substrate oxidation curves, resulting in lower fat oxidation at FATmax, and an increase in the rate of carbohydrate oxidation (Monferrer-Marín et al, 2022). Metabolic exibility (or in exibility) is linked to mitochondrial function, but it has an impact beyond the metabolic effect, as it directly associates with cardiovascular health (Wang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…As age increases, body flexibility tends to decrease. Several studies have shown that aging is associated with a reduction in joint range of motion and flexibility (23).…”
Section: Discussionmentioning
confidence: 99%